КОРРЕКТНЫЕ МОДЕЛИ ИЗ ЛИНЕЙНОГО ЗАМЫКАНИЯ МОДЕЛИ ВЫЧИСЛЕНИЯ ОЦЕНОК - Кабулов, А.В.; Бабаджанов, А.Ф.; Сайманов, И. (SCIENCE and SOCIETY, 2022)
In this paper, we study an algorithmic model for calculating estimates and prove the existence of an optimal algorithm in this model. For problems with disjoint classes is constructed a much simpler in description and much more efficient computational algorithm. Methods are being developed that make it possible to code operator B more economically, which will reduce the required memory and more efficiently use the constructed correct algorithms for solving applied problems.